Profitability of replacing milk with a concentrate for calves of cows requiring calf at foot for milking - Ouologuem, B.; Reese, A.A.; Traoré, A.; Debrah, S.K. (Springer, 1994)
During a 90-day study in Mali, West Africa, 18 Zebu by Montbeliond calves, age 50 + 23d, weighing 30 + 7 kg, under farmer management, were used to test the profitability of replacing suckled milk by a maize - groundnut cake-rice bran concentrate fed dry. During the first 45d period there were no differences in responses of calves receiving concentrate (E) and calves suckling according to the traditional strategy (c). During the second 45d period, milk offtake was greater for E calves, 2.34 vs. 1.77 l/d; milk suckled was less for E calves, 0.39 vs. 0.95 l/d; and average daily gain was greater for E calves, 442 vs. 139 g/d. Average concentrate consumption was 0.74 kg/d. Concentrate was compounded of locally available byproducts and cost 85 francs/kg. Considering milk sold as the only benefit, net return to unit feed cost for E calves was 1.24 and for C calves 0.81. Adding the value of the weight gain, E. calves was 1.24 and for C calves 0.81. Adding the value of the weight gain, E calves gave a 1.61 return and C calves gave a 0.98 return.